Suitability of Free-Living Marine Nematodes as Bioindicators: Status and Future Considerations - Ridall, Aaron; Ingels, Jeroen (Frontiers in Marine Science, 2021)
Nematodes are among the most abundant organisms on Earth, and have important roles in terrestrial, freshwater, and marine ecosystems. Free-living marine nematodes have been used successfully as indicators of biological health and ocean pollution for at least the past 40 years, but their use as bioindicators is not ubiquitous. They have been most often used specifically as indicators of heavy metal and hydrocarbon pollution, with far fewer instances of their use as indicators of biological, environmental, or physical perturbations. Although free-living marine nematodes are among the best bioindicators owing to their worldwide distributions, abundances, and genus- and species-specific responses to environmental pollution, there are still some challenges that prevent their use globally. Here, we present a review of characteristics that make free-living marine nematodes excellent bioindicators, recent studies that have used them as bioindicators, and suggestions for future directions in the use of these fauna as indicators in the marine environment. Specifically, we consider the use of marine nematodes for microplastics (an understudied class of pollutants that are a future threat to global biodiversity), the value of current nematode indices as measures of ecosystem health, and the importance of improved and continued international collaboration in the field of marine nematology.